Conceptualizing context in entrepreneurship education: a literature review. Issue 5 (2nd September 2019) - Thomassen, Mette Lindahl; Williams Middleton, Karen; Ramsgaard, Michael Breum; Neergaard, Helle; Warren, Lorraine
Abstract : Purpose: Context impacts the design and practice of entrepreneurship education, but there is limited focus on context in entrepreneurship education literature. The purpose of this paper is to review the entrepreneurship education literature to understand how context has been addressed, derives contextual elements from prioritized literature and explores how context can be adapted to and designed with in entrepreneurship education. Design/methodology/approach: A systematic literature review is undertaken to explore context in entrepreneurship education literature. Context entrepreneurship education yielded 239 items. After refinement, 232 entrepreneurship education associated publications were reviewed by the team of authors. Using selection criteria, 26 prioritized publications were analyzed and categorized according to a theoretical framework. Findings: Context has been addressed both conceptually and empirically, quantitatively and qualitatively, and can be categorized across three sociological phenomena levels – micro, meso and macro. Within these levels, more specific context elements emerge from the entrepreneurship education literature. The findings assert that while context is highly influential in relation to entrepreneurship education, it is arbitrarily described, and holds a variety of documented and diffuse elements. Educators have a limited span of control in relation to context elements, however, for the most parts elements can be adapted to or designed with. Finally, due to the influence of context it is difficult to identify a universal best practice of entrepreneurship education because there simply is no ceteris paribus . Research limitations/implications: Contextual elements which emerged from the literature consider various subjects, spaces, structures and networks. Context is complex and has had limited treatment in entrepreneurship education literature, thus additional analysis and experimentation is necessary. Practical implications: Context shapes understanding and influences learning. Addressing entrepreneurship education across three levels – micro, meso and macro – and through four framing questions – who, what, where and when – guides educators in how context influences and can be used when designing education. Originality/value: The paper gives new insight into how context is addressed in entrepreneurship education literature, and how this can influence educational design.